Пиналъёслы кылбуръёс - Михалков Сергей Владимирович (Удмуртское книжное издательство, 1953)
Экземпляры: КР (20020330) / Инвентарный номер: у7120 / Сис.шифр: Р2 / Авт.знак: М 69 / ГРНТИ: 17.82 / ББК: 84(2)